2019
DOI: 10.1111/sum.12484
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sugarcane filter cake on the availability of P in the rhizosphere and associated microbial community structure

Abstract: This study aimed to evaluate the interaction between filter cake (FC), and phosphorus fertilizers with differing solubility on the growth and P nutrition of sugarcane.Effects of soil amendment with FC on different soil P fractions and influence on microbial community structure in the rhizosphere were also assessed. Two glasshouse experiments were conducted with completely randomized block designs. The first experiment evaluated rates of FC using a factorial design (5 × 2): 0, 2.5, 5, 10 and 15 g FC kg −1 soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Previous studies performed under controlled conditions already demonstrated the potential of PGPBs to improve sugarcane yields [53]. Also, the positive effect of PGPBs on plant biomass and nutrition has been observed in soils with low P availability [48].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies performed under controlled conditions already demonstrated the potential of PGPBs to improve sugarcane yields [53]. Also, the positive effect of PGPBs on plant biomass and nutrition has been observed in soils with low P availability [48].…”
Section: Discussionmentioning
confidence: 96%
“…Among other factors, soil microbial communities are affected by the availability of nutrients corresponding to the type of soil management practice (Bolan et al, 1996;Lauber et al, 2009;Leff et al, 2015). For example, the use of soluble fertilizers (e.g., monocalcium phosphate), less soluble organic fertilizer (e.g., sugarcane filter cake) or nearly insoluble rock phosphate (Arruda et al, 2019) have different impacts on soil microbial communities. Soil management practices also affect soil hydraulics, which affects plant and microbial biodiversity and ecosystem resilience (Alley et al, 2002;Anderegg et al, 2018).…”
Section: Soil Biodiversitymentioning
confidence: 99%
“…Phosphorus in FC is mostly organic and must be mineralized over two or three seasons to supply P for plant uptake, but research suggests that FC can be partially or fully substituted for inorganic P fertilizer at planting without confounding crop yields or the build‐up rates of soil P fertility (Caione et al, ; Elsayed, Babiker, Abdelmalik, Mukhtar, & Montange, ). Additional benefits in conserving soil moisture and microbial diversity have also been observed; for example, Arruda et al () found that FC modified the structure of fungal and bacterial communities, whereas only bacterial and archaea communities were influenced by mineral P fertilizer use. Realizing effective substitution is dependent on the cost of transporting FC to surrounding farmland, and recycling distances from the mills are currently 20–30 km.…”
Section: R Options For the Sustainable Management Of P In Sugarcanementioning
confidence: 99%